2019
DOI: 10.1016/j.euf.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset Hypogonadism and Testosterone Therapy – A Summary of Guidelines from the American Urological Association and the European Association of Urology

Abstract: Men with low serum testosterone and symptoms of androgen deficiency may be diagnosed with testosterone deficiency. This condition is associated with metabolic syndrome and cardiovascular disease. The benefits (eg, improvement in sexual function) and risks (eg, prostate cancer and cardiovascular disease) of testosterone therapy are controversial. The American Urological Association and European Association of Urology guidelines on testosterone therapy differ on several points of management, likely reflecting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 64 publications
0
29
0
1
Order By: Relevance
“…Late-onset hypogonadism or testosterone deficiency may result in significant detriment to quality of life, and adversely affect the function of multiple organ systems [4]. In a systematic review and metaanalysis, consisting of the 21 studies, Araujo et al [6] demonstrated that difference in the means of the top and bottom third of the standard normal distribution in total testosterone was associated with 35 and 25% increased risk of all-cause and cardiovascular disease mortality, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Late-onset hypogonadism or testosterone deficiency may result in significant detriment to quality of life, and adversely affect the function of multiple organ systems [4]. In a systematic review and metaanalysis, consisting of the 21 studies, Araujo et al [6] demonstrated that difference in the means of the top and bottom third of the standard normal distribution in total testosterone was associated with 35 and 25% increased risk of all-cause and cardiovascular disease mortality, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone is the principal male sex hormone, and decreases on average by 0.8-2% per year after the age of 40 years. The prevalence of male hypogonadism has been ranged from 2.1 to 9.5% in men aged 40-70 years [4][5][6]. Its rate significantly increases, ranging 10-80% in several morbid diseases [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Late-onset hypogonadism (LOH) is associated with advancing age and is characterised by symptoms of androgen deficiency and low serum testosterone 1. Hypogonadism with clinical symptoms can lead to decline in exercise tolerance and muscle mass and an attenuation of bone strength, which may significantly reduce quality of life 2.…”
Section: Introductionmentioning
confidence: 99%
“…These results don’t support a protective role of TRT towards patients with a history of PCa, but encourage broaden research in this way. 91 , 94 …”
Section: Effects Of the Treatment In Patients With Prostatic Diseasesmentioning
confidence: 99%